Para a língua voltar: o papel da política e cultura linguística no processo de fortalecimento da Língua Apurinã (Aruák) - BARROS, Jeanne Barros de (Universidade Federal do Pará, 2019)
This research aims to survey the current state of the art of language teaching in Apurinã (Arawak), and to describe and analyze the main aspects of the Apurinã language policy and culture in its strengthening process. For almost 30 years the Apurinã language has been documented and described, a work which made possible some actions for the strengthening of the language in the communities. These initiatives involved the production of pedagogical materials co-authored with speakers of the Apurinã language and linguists. The present work has the Apurinã indigenous teachers as main sources of information. It seeks to update information about language teaching in the school context, since the school and writing in the language are considered by these teachers, as well as but representatives of the Apurinã Indigenous communities, as important tools in the process of language strengthening and maintenance. We also investigate, in the school context, aspects of language policy (uses, linguistic choices) and linguistic culture (ideologies and beliefs) that are determinant to the process of linguistic strengthening as they correlate with conceptions and attitudes towards the processes of language change, teaching or non-teaching of languages. The methodological procedures used include the literature review on studies of Linguistic Policy and Linguistic Culture and its relations with language strengthening. We also consider studies on Linguistic Policies directed at Brazilian Indigenous peoples, the meanings and representations of writing in the processes of Indigenous schooling and analysis of data collected in field trips in the months of March and September of 2017. This work therefore brings together information on initiatives to strengthen the language in a school context, reflections on the linguistic and ideological choices that the Apurinã people make and how they can benefit the initiatives of strengthening and maintenance of the Apurinã language by its people.